Maternal obesity, environmental factors, cesarean delivery and breastfeeding as determinants of overweight and obesity in children: results from a cohort - Portela, Daniel S. (2015)
Background:Overweight and obesity are a public health problem with a multifactorial aetiology. The objective of this study was to evaluate risk factors for overweight and obesity in children at 6 years of age, including type of delivery and breastfeeding. Methods: This study relates to a cohort of 672 mother-baby pairs who have been followed from birth up to 6 years of age. The sample included mothers and infants seen at all ten maternity units in a large Brazilian city. Genetic,socioeconomic, demographic variables and postnatal characteristics were analyzed. The outcome analyzed was overweight and/or obesity defined as a body mass index greater than or equal to +1 z-score. The sample was stratified by breastfeeding duration, and a descriptive analysis was performed using a hierarchical logistic regression. P-values of <0.05 were considered significant. Results:Prevalence rates (PR) of overweight and obesity among the children were 15.6% and 12.9%, respectively. Among the subset of breastfed children, factors associated with the outcome were maternal overweight and/or obesity (PR 1.92; 95% confidence interval“ 95% CI”1.15–3.24) and lower income (PR 0.50; 95% CI 0.29–0.85). Among children who had not been breastfed or had been breastfed for shorter periods (less than 12 months), predictors were mothers with lower levels of education (PR 0.39; 95% CI 0.19–0.78), working mothers (PR 1.83; 95% CI 1.05–3.21), caesarean delivery (PR 1.98; 95% CI 1.14– 3.50) and maternal obesity (PR 3.05; 95% CI 1.81–5.25).Conclusions: Maternal obesity and caesarean delivery were strongly associated with childhood overweight and/or obesity. Lower family income and lower levels of education were identified as protective factors. Breastfeeding duration appeared to modify the association between overweight/obesity and the other predictors studied.